Methods and facilities of construction of analog-digital coders of the special processors of the cross-correlation working of signals - Albanskiy, Ivan (Видавництво Львівської політехніки, 2010)
Theoretical bases are expounded and systematized architecture of analog-digital coders of the cross-correlation working of signals.
Keywords: Coders; cross-correlation; teoretiko numerical base